2021
DOI: 10.1016/j.media.2021.101972
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric disease classification using functional connectomics - results of the connectomics in neuroimaging transfer learning challenge

Abstract: This is a repository copy of Neuropsychiatric disease classification using functional connectomics -results of the connectomics in neuroImaging transfer learning challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Out of the three parcellation schemes, the AAL atlas provides slightly better classification accuracy, which illustrates that the parcellation scheme can have an effect on the manner in which the network features are associated with the clinical outcome. We note that the classification accuracy reported in our analysis are comparable, and often higher compared to the results reported for the same dataset in [26]. In addition, the classification performance using dynamic connectivity based on sliding windows appear less accurate compared to the static connectivity results, that is consistent with our findings from the HCP study (not reported due to space constraints).…”
Section: Analysis Results For Cni Datasupporting
confidence: 88%
See 2 more Smart Citations
“…Out of the three parcellation schemes, the AAL atlas provides slightly better classification accuracy, which illustrates that the parcellation scheme can have an effect on the manner in which the network features are associated with the clinical outcome. We note that the classification accuracy reported in our analysis are comparable, and often higher compared to the results reported for the same dataset in [26]. In addition, the classification performance using dynamic connectivity based on sliding windows appear less accurate compared to the static connectivity results, that is consistent with our findings from the HCP study (not reported due to space constraints).…”
Section: Analysis Results For Cni Datasupporting
confidence: 88%
“…In our analysis we used 120 ADHD children after excluding those with the ASD diagnosis, and matched this cohort with another 120 NC subjects. The data was downloaded from the Github repositories that are provided in [26]. The acquisition protocol for the rs-fMRI data used a single shot, partially parallel gradient-recalled EPI sequence with TR/TE 2500/30ms, flip angle 70 degrees, and voxel resolution 3.05 × 3.15 × 3mm 3 on a Philips 3T Achieva scanner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used open‐source 240 resting‐state fMRI (rsfMRI) time series data from the Connectomics in NeuroImaging Transfer Learning Challenge (CNI‐TLC) [ 54 ] for connectome analysis and diagnosis of ADHD. First, each rsfMRI time series was averaged according to the AAL [ 55 ] standard parcellation atlas.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic learning can help AI models to be continuously augmented based on expert’s feedback. Transfer learning is where a model trained with another dataset is fine-tuned over the target dataset [ 41 , 42 ]. Transfer learning is an effective approach when sufficient data is not available to train the model from scratch.…”
Section: Machine Learningmentioning
confidence: 99%